Comparison of objective visual quality between SMILE and FS-LASIK in moderate-to-high myopia - Zou, Huaxian; Wei, Xianxian; Li, Lili; Wei, Diefeng; Mao, Hejuan; Huang, Yanyan; Lu, Pengfei; Li, Ziyu; Zhong, Dedong; Chen, Qi (Frontiers in Medicine, 2024)
Purpose: To compare the changes in the corneal wavefront aberrations and the objective visual quality after small incision lenticule extraction (SMILE) and femtosecond laser-assisted in situ keratomileusis (FS-LASIK) in patients with moderate-to-high myopia.Methods: Prospective analysis was performed on 98 eyes of 51 patients who underwent SMILE. 88 eyes of 45 patients who underwent FS-LASIK were analyzed. All patients underwent ocular examination preoperatively and at 1 day, 1 week, 1 month, and 3 months postoperatively. Corneal aberrations and objective visual quality were measured using the OQAS II and OPD-Scan Ⅲ.At postoperative 1 day and 1 week, there was statistically significant in uncorrected distance visual acuity (UDVA) between SMILE and FS-LASIK(P<0.05). Postoperative spherical (S), cylinder (C) and spherical equivalent refraction (SE) was similar between the two groups (P>0.05). In both groups, the absolute absolute magnitude of tHOA, piston, vertical tilt, vertical coma, and spherical aberration (SA) increased after surgery compared to preoperative values (P<0.05). There was no significant difference in Δhorizontal tHOA, Δhorizontal tilt, Δhorizontal coma, and Δhorizontal trefoil between the two groups (P>0.05), and the FS-LASIK had higher Δvertical trefoil and ΔSA(P<0.05) but lower Δpiston and Δvertical coma than the SMILE group(P<0.05). There was a rise in OSI and a decline in both MTF cutoff and SR after surgery compared to preoperative values in both groups (P<0.05). There was a statistically significant difference in the OSI at 1 day and 3 months between the two groups (P<0.05). Postoperative MTF cutoff and SR were similar between the two groups (P>0.05). Postoperative OSI was positively correlated with corneal tHOA (0.261≤R≤0.483, P<0.05), and was negatively correlated with vertical tilt and vertical coma (-0.315≤R≤-0.209, P<0.05) in both groups. Conclusions: Both SMILE and FS-LASIK can effectively correct moderate-to-high myopia, there is an increase in corneal aberrations and a postoperative delay in objective visual quality. The cornea may require a longer recovery period in the SMILE. OPD-Scan Ⅲ combined with OQAS Ⅱ is a useful supplementary inspection for assessing the optical quality following refractive surgery.